2020
DOI: 10.1002/lary.29157
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Post‐Tonsillectomy Opioid Prescribing Practices

Abstract: Objective: To evaluate the effect of discharge order sets on prescribing patterns of opioids after pediatric tonsillectomy. Secondary outcomes included encounters for postoperative pain, dehydration, and bleeding.Methods: Retrospective chart review of pre-and post-intervention in pediatric post-tonsillectomy patients, 0-18 years old (n = 1486). Order sets were installed with age-specific analgesic medication defaults and recommendation of concurrent alternating scheduled ibuprofen and acetaminophen. Time-balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…After provider education and implementing our standardized dosing protocol at BCSC, the average number of oxycodone doses per patient decreased significantly and there were no significant differences in rates of refill requests, 7‐day ED visits, or readmissions. The effects of reducing and eliminating opiates in posttonsillectomy patients have been studied, and our results are consistent with previous reports 4,18‐26 . Cordray et al implemented a similar opiate‐sparing protocol and studied its effects on both prescribing habits and outcomes in 1817 tonsillectomy patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…After provider education and implementing our standardized dosing protocol at BCSC, the average number of oxycodone doses per patient decreased significantly and there were no significant differences in rates of refill requests, 7‐day ED visits, or readmissions. The effects of reducing and eliminating opiates in posttonsillectomy patients have been studied, and our results are consistent with previous reports 4,18‐26 . Cordray et al implemented a similar opiate‐sparing protocol and studied its effects on both prescribing habits and outcomes in 1817 tonsillectomy patients.…”
Section: Discussionsupporting
confidence: 91%
“…The effects of reducing and eliminating opiates in posttonsillectomy patients have been studied, and our results are consistent with previous reports. 4,[18][19][20][21][22][23][24][25][26] Cordray et al implemented a similar opiate-sparing protocol and studied its effects on both prescribing habits and outcomes in 1817 tonsillectomy patients. Poststandardization, the average opioid dose per prescription decreased by 16.7 doses (P < .001), interpatient variance decreased significantly (P < .001), and there was no significant increase in the incidence of return to the system for pain or reduced oral intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to legislation, multiple studies have shown that the implementation of institutional protocols, including electronic health record order sets can reduce variability in opioid prescriptions. Two publications reported this specifically for pediatric tonsillectomy 37,38 . It has been well described that high variation in perioperative prescribing is a major contributor to the supply side of the opioid pool 9 .…”
Section: Discussionmentioning
confidence: 99%